2020
DOI: 10.1371/journal.pone.0237130
|View full text |Cite
|
Sign up to set email alerts
|

Clinical, radiological and therapeutic characteristics of patients with COVID-19 in Saudi Arabia

Abstract: Background Coronavirus disease 2019 (COVID-19) is a rapidly spreading global pandemic. The clinical characteristics of COVID-19 have been reported; however, there is limited research investigating the clinical characteristics of COVID-19 in the Middle East. This study aims to investigate the clinical, radiological and therapeutic characteristics of patients diagnosed with COVID19 in Saudi Arabia. Methods This study is a retrospective single-centre case series study. We … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
56
3
4

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 67 publications
(66 citation statements)
references
References 28 publications
3
56
3
4
Order By: Relevance
“…Severe disease. Ten studies reported severe disease as an outcome in COVID-19 patients (19,(54)(55)(56)(57)(58)(59)(60)(61)(62). The definition of severe disease, however, varied among studies.…”
Section: Resultsmentioning
confidence: 99%
“…Severe disease. Ten studies reported severe disease as an outcome in COVID-19 patients (19,(54)(55)(56)(57)(58)(59)(60)(61)(62). The definition of severe disease, however, varied among studies.…”
Section: Resultsmentioning
confidence: 99%
“…In all, 68 studies [ 4 , 17 83 ] were published in English and 1 study [ 84 ] published in Chinese. Out of which 54 studies [ 4 , 18 24 , 29 31 , 34 39 , 45 53 , 55 , 56 , 59 84 ] were from China, 3 studies [ 17 , 32 , 54 ] were from the USA, 3 studies [ 25 , 40 , 44 ] were from Korea, 2 studies [ 26 , 27 ] were from Italy and the remaining 7 studies [ 28 , 33 , 41 – 43 , 57 , 58 ] were from Austria, Iran, Israel, Saudi Arabia, Spain, Turkey, and UK. The sample size per study ranged from 27 to 1590 (total 17 879; 9686 males).…”
Section: Resultsmentioning
confidence: 99%
“…The sample size per study ranged from 27 to 1590 (total 17 879; 9686 males). Considering methodological quality in items of NOS scale, 23 studies [ 4 , 17 , 19 , 21 , 24 , 27 29 , 33 , 34 , 37 , 46 , 49 , 55 , 58 , 61 , 65 , 67 69 , 73 , 75 , 76 ] were rated as high quality (>7 stars) and 46 studies [ 18 , 20 , 22 , 23 , 25 , 26 , 30 32 , 35 , 36 , 38 45 , 47 , 48 , 50 54 , 56 , 57 , 59 , 60 , 62 64 , 66 , 70 72 , 74 , 77 84 ] were rated as moderate quality (5−7 stars). The detailed characteristics and quality of the included studies are summarised in Table 1 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…While such measures are intended to protect people from the infection, a key and unintended consequence of such instructions could be an increase in stress, loneliness and domestic violence among the whole population (Algunmeeyn et al, 2020;Piquero et al, 2020). A recent study conducted in Jordan on more than 4,000 participants found that the COVID-19 pandemic is negatively affecting the mental health of the Jordanian population, causing anxiety and depression in a considerable proportion of the population (Naser et al, 2020). Social relationships and connections enable individuals to regulate their emotions, cope with stress, and remain resilient during stressful situations.…”
Section: Introductionmentioning
confidence: 99%